Free Flap Salvage Using Extracorporeal Tissue Plasminogen Activator Administration: A Comparative Study - Anna Johansen, MS; Martin Halle, PhD, MD; Stina Rittri, PhD, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Flap thrombosis is a challenging complication in free flap surgery, which if untreated will lead to flap failure. Besides mechanical thrombectomy, the potential benefit of thrombolytic therapy with tissue plasminogen activator (tPA) in flap salvage surgery remains uncertain. We hypothesized that extracorporeal tPA administration combined with surgical revision would lead to fewer flap necroses without increased bleeding complications. Methods:. A retrospective study involving 1308 free flaps was conducted, including 42 patients who underwent surgical revision due to established flap thrombosis. The administration of tPA was analyzed in relation to the outcome variables: total and partial flap necrosis, secondary blood transfusion, and exploration for a hematoma or a new thrombosis. Results:. Twenty-two patients received tPA during reexploration, and 20 patients did not. In the tPA group, 9 (41%) total flap failures occurred, and 4 (18%) flaps experienced partial flap necrosis. By comparison, in the tPA naive group, there were 4 (20%) total flap failures and 2 (10%) with partial flap necrosis (not significant). No differences were found in terms of the need for blood transfusion, secondary reexploration for bleeding, or a new thrombosis between the tPA and tPA naive groups. Conclusions:. We did not find that tPA reduced the risk for flap necrosis, nor did it increase the risk for secondary bleeding-related adverse effects. We believe that there was a selection bias toward more severely compromised flaps receiving tPA. We consider extracorporeally administrated tPA in the flap to be safe and a valuable tool in flap salvage surgery.